Colorectal Hamartoma Presenting As a Perineal Mass in a Boy with Proximal Hypospadias - Katja P. Wolffenbuttel (European Journal of Pediatric Surgery Reports, 2020)
Congenital perineal lesions are rare and can occur along with other birth defects such as anorectal malformations (ARMs) and urogenital anomalies. A colorectal hamartoma associated with a urogenital anomaly without ARM is extremely rare. We recently treated a newborn with posterior hypospadias and a solid perineal mass diagnosed as a colorectal hamartoma.